Rising wage inequality and the U.S. gender gap - Blau, Francine D.; Kahn, Lawrence M. (American Economic Review, 1994)
The U.S. labor market has recently experienced two dramatic trends: a falling male-female pay gap and a rising level of labor-market inequality. After decades of near-constancy at about 60 percent, the ratio of women's to men's pay has risen steadily since the late 1970's. At the same time, there were substantial increases in overall wage inequality for both men and women (Lawrence F. Katz and Kevin M. Murphy, 1992; Blau and Kahn, 1993). Wage inequality rose both within and between education and experience groups, and this has been interpreted as reflecting primarily higher returns to both measured and unmeasured labor-market skills (Katz and Murphy, 1992; Chinhui Juhn et al., 1993). This paper addresses the connection between these two important developments. When analyzing gender differentials in pay, economists commonly focus on malefemale differences in skills and on differences in the treatment of equally qualified men and women (i.e., discrimination). Both of these may be considered gender-specific factors influencing the pay gap. Research on these gender-specific factors suggests that women tend to be less skilled than men, on average, and to be located in lower-paying industries and occupations. This in turn suggests that overall wage structure can also have an important effect on the gender pay gap. (Wage structure describes the array of prices set for various labor-market skills, measured and unmeasured, and the rents received for employment in particular sectors of the economy.) For example, since women on average have less experience than men, an increase in the return to experience (as in fact occurred over the 1970s and 1980s) would cause the gender pay gap to rise, even if women's relative level of experience and their gender-specific treatment by employers remained the same. Similarly, an increase in the returns to employment in male occupations and industries would widen the gender differential, all else equal. In earlier work, we found overall wage inequality to be very important in explaining international differences in the gender pay gap (Blau and Kahn, 1992, 1994). In particular, we addressed a paradox. On the one hand, U.S. women compare favorably to those in other countries in terms of their relative qualifications and occupational status. Further, the United States has had a longer and often stronger commitment to equal pay and equal employment policies than most other industrialized countries. Yet the gender pay gap in the United States is larger than in most of these countries. An important part of the explanation for this pattern is the high level of wage inequality (i.e., high returns to skill) in the United States, which puts an exceptionally large penalty on being below average in the wage distribution. Our results suggest that the U.S. gap would be similar to that in countries like Sweden or Australia (the countries with the smallest gaps) if the United States had their level of wage inequality. The implication of our earlier research on international differences in the gender gap is that in recent years American women have been swimming upstream in a labor market that was growing increasingly unfavorable to low-wage workers. In the face of this rising inequality, women's relative skills and treatment have to improve merely for the pay gap to remain constant; still larger gains are necessary for it to be reduced. * Blau: Institute of Labor and Industrial Relations, University of Illinois, Champaign, IL 61820, and NBER; Kahn: Institute of Labor and Industrial Relations, University of Illinois. We thank Claudia Goldin and participants at the NBER Labor Studies meeting and the University of Illinois and Cornell Labor Economics Workshops for helpful comments, and Jennifer Berdahl for excellent research assistance. Portions of this work were completed while the authors were visiting fellows at the Australian National University, Canberra.